Corticomotor Responses to Attentionally Demanding Motor Performance: A Mini-Review - Corp, Daniel T.; Drury, Hannah; Young, Kayleigh; Do, MIchael; Perkins, Tom; Pearce, Alan J. (Frontiers in Psychology, 2013)
Increased attentional demand has been shown to reduce motor performance, leading to increases in accidents, particularly in elderly populations. While these deficits have been well documented behaviorally, their cortical correlates are less well known. Increased attention has been shown to affect activity in prefrontal regions of the cortex. However there have been varying results within past research investigating corticomotor regions, mediating motor performance. This mini-review initially discusses past behavioral research, before moving to studies investigating corticomotor areas in response to changes in attention. Recent dual task studies have revealed a possible decline in the ability of older, but not younger, adults to activate inhibitory processes within the motor cortex, which may be correlated with poor motor performance, and thus accidents. A reduction in cortical inhibition may be caused by neurodegeneration within prefrontal regions of the cortex with age, rendering older adults less able to allocate attention to corticomotor regions.